(untitled) (Update Dental College Journal, 2016)
Gestational diabetes mellitus (GDM) is a different degree of the glucose intolerance that begins during pregnancy. GDM affects maternal and child health and is associated with a potential for preeclampsia, caesarean delivery due to macrosomic baby and type 2 diabetes in the mother, and with higher rates of perinatal mortally and many abnormalities in the infant. Homocysteine is a naturally occurring amino acid. Hyperhomocysteinemia(Hcy) is increased homocysteine levels which are associated folic acid deficiency. Hcy is regulated by several factors including genetically determined metabolic enzyme alteration, nutritional status, underlying disease, certain medication, age and pregnancy. A total of (40 case+40control) 80 patients are included in this study, it was observed that majority 21(52.5%) patients were age belonged to 31-35 years in case group and 17(42.5%) patients were age belonged to 31-35 years in control group. The mean age was found 30.5±4.2 years in case group and 29.05±4.2 years in control group. Majority 19(47.5%) patients had 3rd gravida in case group and 20(50.0%) patients had 3rd gravida in control group. Majority patients BMI belonged to 25-29.9 kg/m2 (over weight) in both groups which was 21(52.5%) in case and 32(80.0%) in control group. The mean BMI was found 28.9±3.4 kg/m2 in case and 28.53±2.9 kg/m2 in control group. The difference was not statistically significant (p>0.05) between two groups. Studies have shown that folate deficiency is associated with increased homocysteine levels in blood. Update Dent. Coll. j: 2016; 6 (1): 01-07